The effectiveness of a proposed training program based on an adaptive e-learning environment in developing productive thinking skills among productive families in Jeddah - Najjar, Hanin Muhammad Zuhair; Al-Harbi, Suhail Salem (Journal of Educational and Psychological Sciences, 2023)
The study aimed to measure the effectiveness of a proposed training program based on an adaptive e-learning environment to develop productive thinking skills among productive families in Jeddah. The study sample consisted of (40) productive families, divided into (10) productive families for the exploratory sample, and (30) for the main sample of the study. (α≤ 0.05) between the average ranks of the total study sample in the pre and post applications in the total productive thinking skills in favor of the post application, and in the light of these results, the study recommended taking advantage of the proposed training program based on an adaptive e-learning environment prepared by the researcher in training productive families outside the study sample, And in other professional environments, regions and societies in the Kingdom of Saudi Arabia.
Keywords: adaptive e-learning; productive thinking; productive families